2013
DOI: 10.1530/erc-13-0187
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic mechanisms in follicular cell-derived thyroid cancer

Abstract: Thyroid cancer incidence is rising annually largely related to enhanced detection and of early stage well-differentiated primary tumors. The prognosis for patients with early stage thyroid cancer is outstanding with most patients being cured with surgery. In selected cases, I-131 is administered to treat known or suspected residual or metastatic disease. Even patients with loco-regional metastases typically have an outstanding long-term prognosis, albeit with monitoring and occasional intervention for residual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 125 publications
0
34
0
1
Order By: Relevance
“…Vimentin overexpression was associated with invasion and nodal metastases (Vasko et al 2007, Phay & Ringel 2013. Hardy et al (2007) examined the Snail family of transcription factors and reported that these were associated with thyroid carcinogenesis.…”
Section: Emt and Cscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vimentin overexpression was associated with invasion and nodal metastases (Vasko et al 2007, Phay & Ringel 2013. Hardy et al (2007) examined the Snail family of transcription factors and reported that these were associated with thyroid carcinogenesis.…”
Section: Emt and Cscsmentioning
confidence: 99%
“…As a great deal of research on EMT is to inhibit cancer cells in the mesenchymal state, these approaches may have stimulatory effects on established metastases or even activate dormant cancer cells. The concept of metastatic dormancy during the metastatic cascade is an important feature of metastatic disease (Phay & Ringel 2013). Metastatic dormancy may include physical barriers provided by extracellular matrices, as well as expression of proteins encoded by metastatic suppressor genes (Phay & Ringel 2013).…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…However, such approaches may have stimulatory effects on existing metastatic foci or may even activate dormant cancer cells. 41,42 The concept of metastatic dormancy during the metastatic cascade is an important feature of metastatic disease. 41 Metastatic dormancy may include physical barriers provided by extracellular matrices or protein expression encoded by suppressor genes.…”
mentioning
confidence: 99%
“…41,42 The concept of metastatic dormancy during the metastatic cascade is an important feature of metastatic disease. 41 Metastatic dormancy may include physical barriers provided by extracellular matrices or protein expression encoded by suppressor genes. The goals of understanding the biology of EMT and MET should include designing better drugs to target cancer cells including CSCs more effectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation